Loading...
» »

Further maths Waec Gce 2015 Free Expo




FurtherMaths obj:
1BADBCABADD
11DCBBBCBBDB
21CCADAAADDB
31ADDDBCADDA



4) a=2.5, ar⁴=40
Sbase8=a(r^n-1)/r-1
=2.5(2^8-1)/2-1
=2.5(255)/1
=637.5
r^4=40/2.5
r^4=16
r=2


(6 )
P (x ) = s / n
P (xny) = 2 / 5
P (xny) = p (x ) x p (y)
2 / 5 = 3 / 7 x p(y )
P (y ) = 2 / 5 x 7 / 3 = 14 / 15
(A) p (x) = 14 / 15
(B ) p (xuy) = p (x) + p(x )
= 3 / 7 + 14 / 15
45 + 98 / 105 = 143 / 105



3)

4n-5/(x-2)^2=A/x-2+B/(x-2)^2

4n-5=A(n-2)+B
4n-5=An-2A+B
comparing the coefficient.
A=4, -2A+B=-5
-2(4)+B=-5
-8+B=-5
B=-5+8=3
therefore
4n-5/(n-2)^2=4/n-2+3/(n-2)^2



1) .
F(x )=4 n+ 5 / 2 n+1
G(x )=3 n +1
a . F° g=4 (3 n +1 )+ 5 / 2 (3 x +1 )+1
=12 x + 9 / 6 x+ 3
=1 (4 x +3 )/ 1 (2 x+ 1 )
=4 x+ 3 / 2 x +1
b.
If f° g= h(x )=y
Y =4 x+ 3 / 2 x +1
(2 x +1 )y =4 x + 3
2 xy+ y= 4 n +3
2 xy- 4 x= 3 - y
X =3 - y/ 2 y - 4
X =3 - y/ 2 (y - 2 )
Inverse of f° g=h ^ - 1 (x )= 3 - x / 2 (x - 2 ).



(2)
2^(2x + 2) + 3(2^x) - 1 = 0
2^2x X 2^2 + 3(2^x) - 1 = 0
(2^x)^2 + 3(2^x) - 1 = 0
Let 2^x = y
Y^2 X 4 + 3y - 1 = 0
4y^2 + 3y - 1 = 0
4y^2 + 4y - y - 1 = 0
4y(y+1) - 1(y+1) = 0
(4y-1)(y+1) = 0
4y - 1 = 0 or y + 1 = 0
4y =1 or y= -1
Y = 1/4 or -1
Recall
2^x = y when y = 1/4
2^x = 1/4
2^x = 2^-2
X = -2
When Y = -1
It has bo solution
:- x = -2




FurtherMaths obj:
1BADBCABADD
11DCBBBCBBDB
21CCADAAADDB
31ADDDBCADDA






Related Article


Posted By KellyChi On 10:42 Sat, 10 Oct 2015

Comments:0 || Views:

Comment
Name






.....................

Please LOGIN or REGISTER To Gain Full Access To This Article